The Effects of Urethane on Rat Outer Hair Cells - Mingyu Fu; Mengzi Chen; Xiao Yan; Xueying Yang; Jinfang Xiao; Jie Tang (Neural Plasticity)
The cochlea converts sound vibration into electrical impulses and amplifies the low-level sound signal. Urethane, a widely used anesthetic in animal research, has been shown to reduce the neural responses to auditory stimuli. However, the effects of urethane on cochlea, especially on the function of outer hair cells, remain largely unknown. In the present study, we compared the cochlear microphonic responses between awake and urethane-anesthetized rats. The results revealed that the amplitude of the cochlear microphonic was decreased by urethane, resulting in an increase in the threshold at all of the sound frequencies examined. To deduce the possible mechanism underlying the urethane-induced decrease in cochlear sensitivity, we examined the electrical response properties of isolated outer hair cells using whole-cell patch-clamp recording. We found that urethane hyperpolarizes the outer hair cell membrane potential in a dose-dependent manner and elicits larger outward current. This urethane-induced outward current was blocked by strychnine, an antagonist of the α9 subunit of the nicotinic acetylcholine receptor. Meanwhile, the function of the outer hair cell motor protein, prestin, was not affected. These results suggest that urethane anesthesia is expected to decrease the responses of outer hair cells, whereas the frequency selectivity of cochlea remains unchanged.